Cancer survivors' experiences of humour while navigating through challenging landscapes – a socio‐narrative approach. Issue 4 (10th March 2015) - Roaldsen, Bente Lisbet; Sørlie, Tore; Lorem, Geir F.
Abstract : Aim: Humour is seen as a health‐promoting coping strategy when dealing with life stress. The aim is to elucidate how adult cancer survivors experience and evaluate the significance of humour in daily life, from diagnosis through their entire illness trajectory, and to gain a broader understanding of humour as part of stress‐coping processes during the experience of cancer as a life‐threatening illness. Method: A socio‐narrative approach was chosen to study the humorous stories and their use in everyday contexts. Fourteen participants aged 23–83 with a variety of experiences across diagnoses, times since diagnosis, prognoses and life situations were interviewed. Findings: Participants described humour as helpful and utilised its capacity to deal with difficult situations or related distress, although fluctuations in the course of the illness coincided with two extremes: humour that disappeared and humour that returned. Their use of humour was related to three key themes: facing a life‐threatening situation, togetherness and communication, and living with the situation . Conclusion: Depending on the aim, humour contributes variously through the stress‐coping process within the distinctions of emotion‐, problem‐ and meaning‐focused coping. Humour served to relieve the anxiety burden, enhance problem‐solving ability, safeguard important relationships, communicate difficult topics, regain identity and help significant others to cope, even enabling the richness of life to help living with the risk. Humour should be considered as a significant engaging coping strategy by which the cancer survivors seek to manage their situation throughout the illness trajectory.